2009
DOI: 10.1111/j.1753-6405.2009.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with Aboriginal communities in an urban context: some practical suggestions for public health researchers

Abstract: Objective: In this paper, one Indigenous and two non-Indigenous public health researchers reflect on our combined experience of over thirty years in Aboriginal health, in order to develop some practical guidelines, particularly for researchers working with urban Indigenous population groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 2 publications
0
28
0
Order By: Relevance
“…2005; Menadue 2008). Productive research collaborations must be built on ‘sensitivity’, ‘reciprocity’, ‘respect’, and ‘equality’ (National Health and Medical Research Council 2003; Pyett et al . 2009).…”
Section: ‘White Fella and Black Fella’ Working Together: Building Parmentioning
confidence: 99%
See 1 more Smart Citation
“…2005; Menadue 2008). Productive research collaborations must be built on ‘sensitivity’, ‘reciprocity’, ‘respect’, and ‘equality’ (National Health and Medical Research Council 2003; Pyett et al . 2009).…”
Section: ‘White Fella and Black Fella’ Working Together: Building Parmentioning
confidence: 99%
“…An important prerequisite for these partnerships is the relationship between key individuals (Fuller et al 2005;Menadue 2008). Productive research collaborations must be built on 'sensitivity ', 'reciprocity', 'respect', and 'equality' (National Health and Medical Research Council 2003;Pyett et al 2009). Describing an innovative mental health network and successful collaborative programme between an Aboriginal community and an academic unit in Victoria, McKendrick et al (1990) note that effective partnerships need 'goodwill and a preparedness to work through difficult issues'.…”
Section: 'White Fella and Black Fella' Working Together: Building Parmentioning
confidence: 99%
“…It also received written and verbal approval from the leadership of the Garden Project. Conducting research with urban Aboriginal populations can be challenging because, compared with some rural communities, urban Aboriginal populations may be more dispersed and culturally diverse, lacking any clear council with whom researchers can engage to ensure respectful research (Pyett et al, 2009). For this study, the first author worked closely with the Garden Project steering committee (which consists of project leaders and participants) throughout the study to ensure that the research was carried out in a respectful, useful and participatory manner.…”
Section: Methodsmentioning
confidence: 99%
“…Research teams who have collaborated with Indigenous groups in New Zealand (Tipa et al 2009) and Australia (Pyett et al 2009) on health research initiatives, have reported both similar and additional lessons learned such as flexibility, communication choices, the need to allow for extra time to develop trust and the importance of educating ourselves as researchers about the Aboriginal people and communities we are working with.…”
Section: Individual Versus Focus Group Interviews For Research On Suimentioning
confidence: 92%